Distribution of human Papillomavirus types in women from ethnic minority groups: revealing gaps in South America (Research, Society and Development, 2021)
Objective: To analyze the distribution of intratype varieties of human Papillomavirus in women from minority groups. Methodology: 5 primary studies, published between 2016 and 2019, in English were included. Results: The prevalence of HPV infection in women from minority groups was 31.72%. 54 ethnic groups were surveyed in five countries, Brazil, India, Nigeria and the Netherlands, with two studies conducted in Brazil, one in the state of Maranhão and the other in the state of Pará. The prevalence was between 21.16% and 38.89%. The most frequent HPV genotypes were HPV18, HPV16, HPV31, HPV35, HPV39, HPV45, HPV51, HPV52, and HPV58. Only one research revolution intratype varieties. Conclusion: The prevalence of high-risk HPV ranged between 2% and 8%. The studies did not reveal lineage and sublineage analyzes of HPV 16 and HPV 18. There were few publications using molecular biology methods in Quilombola, Indigenous and Gypsy groups in South American countries considering the relevance of these peoples in cultural formation in Latin countries.